1997
DOI: 10.1023/a:1005782311558
|View full text |Cite
|
Sign up to set email alerts
|

Androgens influence estrogen-induced responses in human breast carcinoma cells through cytochrome P450 aromatase

Abstract: The aromatase cytochrome P450 complex is responsible for the in vivo conversion of androgens to estrogens. Although breast cancer epithelial cells have been reported to have appreciable aromatase activity, its biologic significance remains uncertain. To address this, the effect of androgens on the expression of the estrogen-regulated gene pS2 in hormone-dependent human breast carcinoma cells in vitro was examined. Steroid-deprived MCF-7 cells were exposed to varying concentrations (1 nM, 10 nM, and 100 nM of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 21 publications
5
39
0
4
Order By: Relevance
“…A considerable amount of work has been done over the years studying the effects of androgens on the proliferation of breast cancer cells [1,[7][8][9][10][11][12]. The literature is, however, somewhat confusing, with conflicting data coming from relatively similar experimental systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable amount of work has been done over the years studying the effects of androgens on the proliferation of breast cancer cells [1,[7][8][9][10][11][12]. The literature is, however, somewhat confusing, with conflicting data coming from relatively similar experimental systems.…”
Section: Discussionmentioning
confidence: 99%
“…We were therefore interested in the possibility that androgens and/or their downstream metabolites might play a role in resistance to AI therapy. A number of studies of the effects of androgens on breast cancer cells have been published, with the majority focusing on the effects of testosterone (TS) and 5Îą-dihydrotestosterone (DHT) on breast cancer growth [1,[7][8][9][10][11][12]. Little is known, however, about the effects of these compounds on breast cancer cell growth under conditions of profound estrogen deprivation, similar to conditions found in women treated with AIs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the aromatase gene was found to be amplified in MCF-7 cells, as shown by Southern and DNA slot blot analyses Kitawaki et al (1992) reported that, by converting androgen to estrogen, the endogenous aromatase enzyme in the MCF-7 breast cancer cells (ER-positive cells) could stimulate DNA synthesis, and the stimulation was abolished by the administration of aromatase inhibitors. Burak et al (1997) demonstrated that androgen elicited an estrogen-induced response in MCF-7 cells through aromatase. These results indicate that aromatase, at a level as found in MCF-7 cells, is capable of generating sufficient estrogen to evoke an estrogen-dependent response.…”
Section: Consequence Of Aromatase Expression In Breast Tumorsmentioning
confidence: 99%
“…In postmenopausal women, local aromatization of androgens to estrogens is the main source of estradiol in the tumor and surrounding tissue (Pike et al, 1993;Simpson et al, 1994). These local conversions of estrogens as well as the rate-limiting step of conversion of androstenedione to estrone are catalyzed by the aromatase cytochrome P450 complex (Means et al, 1989;Burak et al, 1997). Clinical ÂŽndings in patients with aromatase deÂŽciency as well as in a knockout mouse (ArKo) lacking functional aromatase, illustrate the role of this enzyme for the development of reproductive organs and mammary glands in female and for the regulation of gonadotropins in both male and female (Harada et al, 1992;Fisher et al, 1998).…”
Section: Introductionmentioning
confidence: 99%